Introduction to Indonesian Culture Through the August 17 Competition at Anuban Wangmai Sasanasart School, Thailand - RIANI, Siti Anggi; PUTRA, Aidil Syah; NARGIS, Nargis (Indonesia Strategic Sustainability, 2025)
In the era of globalization, cross-cultural understanding plays a crucial role in fostering mutual comprehension and tolerance among people worldwide. The International Community Service Program (KKN Internasional), participated in by students from Universitas Muhammadiyah Tangerang (UMT), aims to introduce Indonesian culture to elementary school students in Thailand through traditional Indonesian Independence Day games. This program employs an interactive and enjoyable approach to ensure the effective reception of Indonesian culture. The method involves the active participation of students in various competitions such as water relay, rocking chair, and sarong race. The results indicate that Thai students demonstrate greater enthusiasm and a better understanding of Indonesian culture through direct experience compared to conventional methods. Additionally, this program provides valuable experiences for students in enhancing cross-cultural communication skills, understanding the Thai education system, and strengthening Indonesia-Thailand bilateral relations through cultural diplomacy. This initiative serves as a model for similar programs in other countries, promoting international relations through cultural exchange.